The population and habitat of Tambra fish, Tor tambroides (Bleeker, 1854) in Muller Mountain waters Central Kalimantan - HARYONO HARYONO; JOJO SUBAGJA (Biodiversitas Journal of Biological Diversity, 2008)
Study about tambra fish, Tor tambroides (Bleeker, 1854) or mahseer were conducted in Muller Mountain areas Central Kalimantan. The aims of study were to know status and structure of population, habitat types, and preferences. The methods are catch per unit of effort, visual, and experimental. The results were caught 29 tambra fish, consist of 4 males, 8 females, and 17 juvenile size; the population is rare; the habitat type were grouped to three groups; this fish more prefer to deep waters, the water quality was suitable for living of tambra fish.Key words: tambra fish, Tor tambroides (Bleeker, 1854), population, habitat types, preferences, Muller Mountain.